Transparansi Advokat sebagai Profesi yang Terhormat (Officium Nobile) - Fatimah Zahara; Fikri Fadhilah Fahmi; Mulya Hasbi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This paper aims to provide input on the integrity of advocates, who are free and independent and cannot be separated from their responsibilities based on a code of ethics. This paper is library research, where the approach in this legal research uses statutory and conceptual approaches. The research results show that the behavior of an advocate who adheres to the code of ethics reflects an attitude of obedience to God Almighty, the Law on Advocates, and their Clients. The integrity of an advocate must be fought for, so that it is worthy of being called officium mobile. The integrity of an advocate is seen as having to be on a par with the freedom he gets, his independence, and a sense of responsibility. So that advocates should maintain their integrity as an advocate and behave according to the advocate's code of ethics. However, upholding the code of ethics has so far experienced many obstacles in its enforcement, especially in the absence of a single organization for advocates that is strictly and clearly regulated.. Keywords: Integrity, Advocate, Honorable